2007
DOI: 10.1159/000104800
|View full text |Cite
|
Sign up to set email alerts
|

Caries Prevalence Four Years after the End of a Randomised Controlled Trial

Abstract: This study measured dental caries in children after cessation of a 30-month randomised clinical trial in which the intervention group received supervised toothbrushing once a day at school with 1,000 ppm fluoride toothpaste and a home support package encouraging twice-daily toothbrushing. The non-intervention group did not brush at school or receive the home support package. Children were aged 5 years at baseline and were examined every 6 months during the trial, then at 6, 18, 30 and 54 months after the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 29 publications
0
31
0
1
Order By: Relevance
“…Activity of fluoride toothpastes is based on fluoride concentration, usage frequency, amount of paste used, and habit of mouth washing after brushing [20]. According to the result of a research conducted on children, caries risk is reported to have decreased significantly with a 4.5-year program that comprises brushing with toothpaste containing 1000 ppm fluoride two times a day [24]. On the other hand, individuals with high caries risk are required to use toothpastes containing 5000 ppm fluoride, which has been accepted recently [11].…”
Section: Discussionmentioning
confidence: 99%
“…Activity of fluoride toothpastes is based on fluoride concentration, usage frequency, amount of paste used, and habit of mouth washing after brushing [20]. According to the result of a research conducted on children, caries risk is reported to have decreased significantly with a 4.5-year program that comprises brushing with toothpaste containing 1000 ppm fluoride two times a day [24]. On the other hand, individuals with high caries risk are required to use toothpastes containing 5000 ppm fluoride, which has been accepted recently [11].…”
Section: Discussionmentioning
confidence: 99%
“…Incremental improvements in plaque removal through self‐performed brushing are unlikely to deliver a substantial caries benefit, especially when compared with the benefits of fluoride toothpaste. However, increased brushing frequency has been linked to reductions in caries during clinical trials and the effect of establishing good brushing behaviour has been demonstrated during intervention studies. Further, when behaviour is changed early in life, the caries benefits can continue for many years beyond the intervention period.…”
Section: Towards More Effective and Efficacious Fluoride Toothpastesmentioning
confidence: 99%
“…Further, when behaviour is changed early in life, the caries benefits can continue for many years beyond the intervention period. This caries benefit, resulting from modified behaviour, was also seen in teeth that were unerupted during the intervention period and therefore cannot be attributed to, for example, enhanced fluoride incorporation during post‐eruptive maturation during the intervention period.…”
Section: Towards More Effective and Efficacious Fluoride Toothpastesmentioning
confidence: 99%
“…No obstante, tratándose de una medida preventiva tan importante en el autocuidado de la salud bucodental [7][8][9] sería deseable incrementar ese porcentaje en los próximos años.…”
Section: Cepillado De Dientesunclassified